Lead-based ferroelectric crystal material with high voltage electricity merit figure as well as preparation method and application of lead-based ferroelectric crystal material
By introducing holm oxide dopants into PMN-PT single crystals, the piezoelectric superiority of lead-based ferroelectric crystal materials is improved, and the problem of low piezoelectric superiority of existing lead-based relaxed ferroelectric single crystals is solved, and higher piezoelectric performance is achieved.
Patent Information
- Application Number
- CN202411610082.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lead-based relaxation ferroelectric single crystals are limited in output power in piezoelectric devices, mainly because their piezoelectric voltage coefficient g33 is low, resulting in the piezoelectric superiority d33×g33 below 100pm2/N.
By introducing holm oxide dopant into the single crystal of lead niobium magnesium niobium magnesium titanate (PMN-PT), the B-position of the perovskite structure is introduced using large radius holmium ions to increase the local structure inhomogeneity, and the piezoelectric charge coefficient d33 and the piezoelectric voltage coefficient g33 are improved, thereby improving the piezoelectric superiority.
The piezoelectric superiority of lead-based ferroelectric crystal material is achieved by greater than 160pm2/N, the piezoelectric charge coefficient d33 is between 4000-5000pC/N, and the piezoelectric voltage coefficient g33 is between 0.0405-0.0476Vm/N, which significantly improves the performance of piezoelectric devices.
Smart Images

Figure BDA0005130716070000082
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric materials, and in particular relates to a lead-based ferroelectric crystal material with a high voltage merit, and a preparation method and application thereof. Background Art
[0002] Lead-based relaxor ferroelectric single crystals have high piezoelectric charge coefficients (d 33 ~2000pC / N) and high electromechanical coupling coefficient (k 33 ~90%), and has attracted extensive attention from scholars in this field. Among them, lead magnesium niobate-lead titanate (PMN-PT) and lead indium niobate-lead magnesium niobate-lead titanate (PIN-PMN-PT) single crystals have been used in piezoelectric transducers, actuators and other devices.
[0003] In order to keep up with the development of future technology, it is necessary to develop piezoelectric devices with higher sensitivity and conversion efficiency. 33 and the piezoelectric voltage coefficient g 33 It is a key parameter to measure the performance of piezoelectric devices, usually using the piezoelectric figure of merit d 33 ×g 33 Indicates that the output power of the sensor and piezoelectric energy harvester is related to the piezoelectric voltage coefficient g 33 The piezoelectric voltage coefficient g of lead-based relaxor ferroelectric single crystals is currently 33 <0.04Vm / N, piezoelectric figure of merit d 33 ×g 33 Below 100pm 2 / N, which limits the power output of existing lead-based relaxor ferroelectric single crystals. Therefore, it is necessary to develop a ferroelectric single crystal with both high voltage charge coefficient d 33 and the piezoelectric voltage coefficient g 33 materials, thereby improving the performance of piezoelectric devices.
[0004] Doping modification is an important and practical means of material modification, which has achieved remarkable performance improvements in the fields of electricity, light, magnetism, etc. At present, PMN-PT single crystals doped with rare earth ions (samarium and neodymium) can obtain a higher piezoelectric charge coefficient d 33 , up to 4000pC / N; due to the piezoelectric charge coefficient d 33 It is positively correlated with the dielectric constant. The piezoelectric voltage coefficient g of PMN-PT single crystal doped with rare earth ions is 33 There is no improvement, therefore, a higher piezoelectric figure of merit d 33 ×g 33 The development of piezoelectric materials has always been a challenge. Summary of the invention
[0005] In order to improve the deficiencies of the prior art, the present invention provides a lead-based ferroelectric crystal material with a high voltage merit, a preparation method and an application thereof, wherein the piezoelectric merit of the lead-based ferroelectric crystal material is greater than 160 pm 2 / N.
[0006] The technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a lead-based ferroelectric crystal material with a high voltage merit, wherein the chemical formula of the material is xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 , x, y represent molar fractions, wherein 0.002≤x≤0.02, 0.28≤y≤0.30, the piezoelectric figure of merit d of the lead-based ferroelectric crystal material 33 ×g 33 More than 160pm 2 / N.
[0008] In the embodiment of the present invention, the lead-based ferroelectric crystal material has the following chemical formula:
[0009] (a)0.002Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3 ;
[0010] (b)0.006Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 ;
[0011] (c)0.008Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 ;
[0012] (d)0.02Pb(Ho 1 / 2 Nb1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 .
[0013] According to an embodiment of the present invention, the piezoelectric charge coefficient d 33 4000-5000pC / N, piezoelectric voltage coefficient g 33 0.0405-0.0476Vm / N, piezoelectric figure of merit d 33 ×g 33 164-211pm 2 / N.
[0014] According to an embodiment of the present invention, the lead-based ferroelectric crystal material is a single crystal.
[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned lead-based ferroelectric crystal material with a high voltage electrical merit, comprising preparing the lead-based ferroelectric crystal material with a high voltage electrical merit by a crucible descent method.
[0016] According to an embodiment of the present invention, the preparation method comprises the following steps:
[0017] S1. According to the chemical formula xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 Weighing lead oxide, MgNb 2 O 6 ,HoNbO 4 、TiO 2 As raw materials, x and y have the above-mentioned definitions; a medium is added to the raw materials and ground, dried and calcined to obtain xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 Powder;
[0018] S2. xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )3 -yPbTiO 3 The powder was ground and dried again, pressed into tablets and calcined again to obtain xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 Polycrystalline material;
[0019] S3. Place xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 The polycrystalline material is added into the crystal growth furnace and the crystal is grown by the descending method to obtain xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 Crystal.
[0020] According to an embodiment of the present invention, the medium used in step S1 is anhydrous ethanol or deionized water.
[0021] According to an embodiment of the present invention, the grinding in step S1 is performed by a method known in the art, such as ball milling.
[0022] According to an embodiment of the present invention, the ball milling time is 15 to 30 hours, for example, 24 hours.
[0023] According to an embodiment of the present invention, the drying temperature in S1 is 100-150°C, for example, 100°C.
[0024] According to an embodiment of the present invention, the calcination temperature in step S1 is 800-1100° C., and the calcination time is 2-8 hours, for example, calcination at 850° C. for 4 hours.
[0025] According to an embodiment of the present invention, in step S2, xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3The powder is ground and dried again, including the following steps: xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 The powder is crushed, ground with grinding media, dried, and then ground again.
[0026] According to an embodiment of the present invention, the temperature of the re-calcination in step S2 is 800-1200° C., and the calcination time is 2-8 hours, for example, calcination at 850° C. for 4 hours.
[0027] According to an embodiment of the present invention, step S3 comprises the following steps:
[0028] The xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 The polycrystalline material is placed in a crucible and then placed in a crystal growth furnace. The temperature of the crystal growth furnace is raised to above the melting point of the raw material and kept warm for 5 to 15 hours. Then the crucible is lowered at a rate of 1 to 2 cm / day to grow crystals.
[0029] After a growth period of 15-25 days, the temperature was cooled to room temperature at a rate of 10-40°C / hour to obtain xPb(Ho 1 / 2 Nb 1 / 2 ) 3 -(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -yPbTiO 3 Crystal.
[0030] According to an embodiment of the present invention, before step S1, it also includes preparing MgNb 2 O 6 Powder and HoNbO 4 Powder steps.
[0031] According to an embodiment of the present invention, MgNb is prepared 2 O 6 The powder includes the following steps:
[0032] The raw materials Mg salt or oxide and Nb oxide are added to the grinding medium, ground, dried and crushed, and calcined at a temperature of 1000-1300°C for 1-5h to obtain MgNb 2 O 6 Powder.
[0033] As an example, MgNb 2 O 6 The powder specifically comprises the following steps: raw material MgO or MgCO 3 and Nb 2 O 5 Weigh, add medium and ball mill for 12 hours, then dry at 100°C, grind the dried solid into powder in a mortar, and then calcine the powder in a crucible at 1150°C for 2 hours to obtain MgNb 2 O 6 Powder.
[0034] According to an embodiment of the present invention, HoNbO is prepared 4 The powder includes the following steps:
[0035] Ho oxide and Nb oxide are added to a grinding medium, ground, dried and crushed, and calcined at a temperature of 1000-1300°C for 1-5h to obtain HoNbO 4 Powder.
[0036] As an example, the preparation of HoNbO 4 The powder specifically includes the following steps: 2 O 3 and Nb 2 O 5 The solid was weighed, ball milled for 12 hours with deionized water as the medium, and then dried at 100°C. The dried solid was ground into powder in a mortar, and then the powder was calcined in a crucible at 1150°C for 2 hours to obtain HoNbO 4 Powder.
[0037] In a third aspect, the present invention provides an application of the above-mentioned lead-based ferroelectric crystal material with high voltage electrical merit in piezoelectric devices, for example, as a sensor or a piezoelectric energy collector.
[0038] Beneficial Effects
[0039] By introducing holmium oxide dopant into a lead magnesium niobate-lead titanate (PMN-PT) single crystal, holmium ions with a larger ion radius than the B-site ion radius are introduced into the B-site of the perovskite structure of the lead magnesium niobate-lead titanate (PMN-PT) single crystal, the inhomogeneity of the local structure is increased and the B-site structural space of the perovskite material is reduced, polarization rotation is promoted and oxygen octahedron distortion is induced under the action of an electric field, and the piezoelectric charge coefficient and piezoelectric voltage coefficient of the single crystal are increased to obtain a larger piezoelectric figure of merit; the piezoelectric charge coefficient d of the lead-based ferroelectric crystal material of the present invention is 1.34×10-1.5, and the piezoelectric voltage coefficient ... 33 4000-5000pC / N, piezoelectric voltage coefficient g 33 The piezoelectric performance figure of merit is 0.0405-0.0476Vm / N. 33 ×g 33 164-211pm 2 / N. Compared with the reported lead-based perovskite ferroelectric materials, the crystal material in the present invention has a higher piezoelectric figure of merit and has potential advantages in the manufacture of sensors and piezoelectric energy collectors. DETAILED DESCRIPTION
[0040] The crystal material of the present invention and its preparation method and application will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only for exemplary description and explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0041] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0042] The present invention utilizes structural design to introduce large-radius holmium ions into the B-site of the perovskite structure of lead magnesium niobate-lead titanate (PMN-PT) single crystal, thereby increasing the inhomogeneity of the local structure and reducing the structural space of the B-site of the perovskite material, while also improving the piezoelectric charge coefficient and the piezoelectric voltage coefficient, thereby achieving a larger piezoelectric figure of merit.
[0043] Example 1
[0044] This embodiment uses the crucible descent method to prepare a lead-based ferroelectric crystal material with a high voltage electrical merit, and the preparation is specifically carried out in the following steps:
[0045] a. Weigh 37.227g MgO and 247.371g Nb 2 O 5 The solid was ground into powder in a mortar with anhydrous ethanol as the medium for 12 hours, and then dried at 100 ° C. The powder was then placed in a crucible and calcined at 1150 ° C for 2 hours to obtain 284.886 g MgNb 2 O6 Powder;
[0046] b. Weigh 0.756gHo of raw material 2 O 3 and 0.532gNb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100 °C. The powder was then placed in a crucible and calcined at 1150 °C for 2 hours to obtain 1.287 g HoNbO 4 Powder;
[0047] c. Raw material ratio: PbO, MgNb 2 O 6 ,HoNbO 4 、TiO 2 According to the chemical formula 0.002Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3 Weigh 910.656g, 284.886g, 1.287g, and 95.844g of PbO and MgNb respectively. 2 O 6 ,HoNbO 4 、TiO 2 As raw materials;
[0048] d. The weighed raw materials in step c were mixed, ball milled in deionized water for 24 hours, and then dried at 100 ° C. The dried solid was ground into powder in a mortar, and then the powder was placed in a crucible and calcined at 850 ° C for 4 hours to obtain 0.002Pb (Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3 Powder;
[0049] e. 0.002Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3The powder was crushed and ball-milled for 24 hours with deionized water as the medium, and then dried at 100°C. The dried solid was ground into powder in a mortar, and then the powder was pressed into a block with a tablet press and calcined in a crucible at 850°C for 4 hours to obtain 0.002Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3 Polycrystalline material;
[0050] f. The polycrystalline material sintered in step e is placed in a columnar platinum crucible and then placed in a crystal growth furnace. The temperature of the crystal growth furnace is raised to 1360°C, kept warm for 10 hours, and then the crucible is lowered at a rate of 2cm / day for crystal growth;
[0051] g. After a 20-day growth period, the temperature was cooled to room temperature at a rate of 30°C / hour to obtain 0.002Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.698Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.3PbTiO 3 Crystal.
[0052] Example 2
[0053] This embodiment uses the crucible descent method to prepare a lead-based ferroelectric crystal material with a high voltage electrical merit, and the preparation is specifically carried out in the following steps:
[0054] a. Weigh 37.547g MgO and 249.498g Nb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100°C. The powder was then placed in a crucible and calcined at 1150°C for 2 hours to obtain 287.335 g of MgNb 2 O 6 Powder;
[0055] b. Weigh 2.267gHo of raw material 2 O 3 and 1.595gNb 2 O 5The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100 °C. The powder was then placed in a crucible and calcined at 1150 °C for 2 hours to obtain 3.862 g HoNbO 4 Powder;
[0056] c. Raw material ratio: PbO, MgNb 2 O 6 ,HoNbO 4 、TiO 2 According to the chemical formula 0.006Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 Weigh 910.656g, 287.335g, 3.862g, and 92.649g of PbO and MgNb respectively. 2 O 6 ,HoNbO 4 、TiO 2 As raw materials;
[0057] d. The weighed raw materials in step c were mixed, ball milled in deionized water for 24 hours, and then dried at 100 ° C. The dried solid was ground into powder in a mortar, and then the powder was placed in a crucible and calcined at 850 ° C for 4 hours to obtain 0.006Pb (Ho 1 / 2 Nb 1 / 2 ) 3 -0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 Powder;
[0058] e. 0.006Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 The powder was crushed and ball-milled for 24 hours with deionized water as the medium, and then dried at 100°C. The dried solid was ground into powder in a mortar, and then the powder was pressed into a block with a tablet press and calcined in a crucible at 850°C for 4 hours to obtain 0.006Pb(Ho 1 / 2 Nb 1 / 2 ) 3-0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 Polycrystalline material;
[0059] f. The polycrystalline material sintered in step e is placed in a columnar platinum crucible and then placed in a crystal growth furnace. The temperature of the crystal growth furnace is raised to 1350°C, kept warm for 10 hours, and then the crucible is lowered at a rate of 2cm / day for crystal growth;
[0060] g. After a 20-day growth period, the temperature was cooled to room temperature at a rate of 30°C / hour to obtain 0.006Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.704Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.29PbTiO 3 Crystal.
[0061] Example 3
[0062] This embodiment uses the crucible descent method to prepare a lead-based ferroelectric crystal material with a high voltage electrical merit, and the preparation is specifically carried out in the following steps:
[0063] a. Weigh 37.973g MgO and 252.333g Nb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100°C. The powder was then placed in a crucible and calcined at 1150°C for 2 hours to obtain 290.6 g of MgNb 2 O 6 Powder;
[0064] b. Weigh 3.023gHo 2 O 3 and 2.126gNb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100 °C. The powder was then placed in a crucible and calcined at 1150 °C for 2 hours to obtain 5.149 g HoNbO 4 Powder;
[0065] c. Raw material ratio: PbO, MgNb 2 O 6 ,HoNbO 4 、TiO 2According to the chemical formula 0.008Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Weigh 910.656g, 290.6g, 5.149g, and 89.454g of PbO and MgNb respectively. 2 O 6 ,HoNbO 4 、TiO 2 As raw materials;
[0066] d. The weighed raw materials in step c were mixed, ball milled in deionized water for 24 hours, and then dried at 100 ° C. The dried solid was ground into powder in a mortar, and then the powder was placed in a crucible and calcined at 850 ° C for 4 hours to obtain 0.008Pb (Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Powder;
[0067] e. 0.008Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 The powder was crushed and ball-milled for 24 hours with deionized water as the medium, and then dried at 100°C. The dried solid was ground into powder in a mortar, and then the powder was pressed into a block with a tablet press and calcined in a crucible at 850°C for 4 hours to obtain 0.008Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Polycrystalline material;
[0068] f. The polycrystalline material sintered in step e is placed in a columnar platinum crucible and then placed in a crystal growth furnace. The temperature of the crystal growth furnace is raised to 1350°C, kept warm for 10 hours, and then the crucible is lowered at a rate of 2cm / day for crystal growth;
[0069] After a 20-day growth period, the temperature was cooled to room temperature at a rate of 30°C / hour to obtain 0.008Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.712Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Crystal.
[0070] Example 4
[0071] The present invention uses a crucible descent method to prepare a lead-based ferroelectric crystal material with a high voltage electrical merit, and specifically adopts the following steps to prepare:
[0072] a. Weigh 37.882g MgO and 249.852g Nb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100°C. The powder was then placed in a crucible and calcined at 1150°C for 2 hours to obtain 287.743 g of MgNb 2 O 6 Powder;
[0073] b. Weigh 7.557g of raw material Ho 2 O 3 and 5.316 g Nb 2 O 5 The solid was ground into powder in a mortar with deionized water as the medium for 12 hours, and then dried at 100 °C. The powder was then placed in a crucible and calcined at 1150 °C for 2 hours to obtain 12.873 g HoNbO 4 Powder;
[0074] c. Raw material ratio: PbO, MgNb 2 O 6 ,HoNbO 4 、TiO 2 According to the chemical formula 0.02Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Weigh 910.656g, 287.743g, 12.873g, and 89.454g of PbO and MgNb respectively. 2 O 6,HoNbO 4 、TiO 2 ;
[0075] d. The weighed raw materials in step c were mixed, ball milled in deionized water for 24 hours, and then dried at 100 ° C. The dried solid was ground into powder in a mortar, and then the powder was placed in a crucible and calcined at 850 ° C for 4 hours to obtain 0.02Pb (Ho 1 / 2 Nb 1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Powder;
[0076] e. 0.02Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 The powder was crushed and ball-milled for 24 hours with deionized water as the medium, and then dried at 100°C. The dried solid was ground into powder in a mortar, and then the powder was pressed into a block with a tablet press and calcined in a crucible at 850°C for 4 hours to obtain 0.02Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Polycrystalline material;
[0077] f. The polycrystalline material sintered in step e is placed in a columnar platinum crucible and then placed in a crystal growth furnace. The temperature of the crystal growth furnace is raised to 1350°C, kept warm for 10 hours, and then the crucible is lowered at a rate of 2cm / day for crystal growth;
[0078] g. After a 20-day growth period, the temperature was cooled to room temperature at a rate of 30°C / hour to obtain 0.02Pb(Ho 1 / 2 Nb 1 / 2 ) 3 -0.7Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -0.28PbTiO 3 Crystal.
[0079] Example 5
[0080] The lead-based ferroelectric crystal materials prepared in Examples 1-4 were subjected to electrical property tests.
[0081] a. Processing (001) surface single crystal: Orient and process the lead-based ferroelectric crystal materials prepared in Examples 1-4 respectively. Use the three-dimensional orientation method to accurately cut into (001) surface 5mm×5mm×0.5mm single crystals. Grind and polish the (001) surface for subsequent use.
[0082] b. Preparation of electrodes: Coat the upper and lower (001) surfaces of the processed single crystal with high-temperature silver paste and sinter at 600°C for electrical performance testing.
[0083] c. Dielectric test: The polarized samples were measured using a broadband dielectric impedance spectrometer Concept40 produced by Novocontrol of Germany to obtain the room temperature dielectric constant of 1 kHz.
[0084] d. Piezoelectric test: Use ZJ-4AN quasi-static piezoelectric instrument to test and obtain the piezoelectric charge coefficient d 33 .
[0085] e. According to the piezoelectric voltage coefficient calculation formula: The piezoelectric properties shown in Table 1 were obtained.
[0086] Table 1 Piezoelectric properties of lead-based ferroelectric crystal materials prepared in Examples 1-4
[0087]
[0088] Table 2 Comparison of piezoelectric merits of lead-based ferroelectric crystal materials prepared in Examples 1-4 and other lead-based ferroelectric materials
[0089] Material <![CDATA[Piezoelectric figure of merit (d 33 × g 33 )]]> PZT-5H ceramic <![CDATA[15pm 2 / N]]> Textured PZT Ceramics <![CDATA[76pm 2 / N]]> PMN-30PT single crystal <![CDATA[98pm 2 / N]]> PMN-28PT single crystal <![CDATA[57pm 2 / N]]> 25PIN-43PMN-33PT single crystal <![CDATA[69pm 2 / N]]> Example 1 <![CDATA[190-210pm 2 / N]]> Example 2 <![CDATA[180-211pm 2 / N]]> Example 3 <![CDATA[180-200pm 2 / N]]> Example 4 <![CDATA[164-195pm 2 / N]]>
[0090] Table 2 is a comparison of the piezoelectric merits of the lead-based ferroelectric crystal material prepared in the embodiment and other lead-based perovskite ferroelectric materials. The lead-based ferroelectric crystal material prepared in the present invention has a high piezoelectric charge coefficient d 33 , high voltage voltage coefficient g 33 And high voltage figure of merit d 33 ×g 33 The piezoelectric figure of merit d of the lead-based ferroelectric crystal material prepared in this embodiment is 33 ×g 33 All above 160pm 2 / N, the highest can reach 211pm 2 / N, where the piezoelectric figure of merit d 33 ×g 33This is higher than the reported lead-based relaxor ferroelectric materials and has potential application value in sensors and piezoelectric energy harvesters.
[0091] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A lead-based ferroelectric crystal material with high voltage merit, characterized in that: The chemical formula of this material is xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3, x, y represent molar fractions, wherein 0.002≤x≤0.02, 0.28≤y≤0.30, the piezoelectric merit d of the lead-based ferroelectric crystal material 33 ×g 33 More than 160pm 2 / N.
2. The lead-based ferroelectric crystal material with high voltage merit according to claim 1, characterized in that: The lead-based ferroelectric crystal material has the following chemical formula: <h2 style=";text-align:left;direction:ltr">(a)0.002Pb(Ho<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )O3-0.698Pb(Mg<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> )O3-0.3PbTiO3; <h2 style=";text-align:left;direction:ltr">(b)0.006Pb(Ho<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )O3-0.704Pb(Mg<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> )O3-0.29PbTiO3; <h2 style=";text-align:left;direction:ltr">(c)0.008Pb(Ho<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )O3-0.712Pb(Mg<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> )O3-0.28PbTiO3; <h2 style=";text-align:left;direction:ltr">(d)0.02Pb(Ho<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )O3-0.7Pb(Mg<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> )O3-0.28PbTiO3。 3. The lead-based ferroelectric crystal material with high voltage merit according to claim 1 or 2, characterized in that: The piezoelectric charge coefficient d of the lead-based ferroelectric crystal material 33 4000-5000pC / N, piezoelectric voltage coefficient g 33 0.0405-0.0476Vm / N, piezoelectric figure of merit d 33 ×g 33 164-211pm 2 / N. Preferably, the lead-based ferroelectric crystal material is a single crystal.
4. A method for preparing a lead-based ferroelectric crystal material with a high voltage merit as claimed in any one of claims 1 to 3, characterized in that: The method comprises the steps of preparing a lead-based ferroelectric crystal material with a high voltage electrical merit by a crucible descent method. Preferably, the preparation method comprises the following steps: S1. According to the chemical formula xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 Weigh lead oxide, MgNb2O6, HoNbO4, and TiO2 as raw materials, where x and y have the above definitions; add a medium to the raw materials and grind them, dry them, and calcine them to obtain xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 powder; S2. xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 powder was ground and dried again, pressed into tablets and calcined again to obtain xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 polycrystalline material; S3. Place xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 polycrystalline material is added into the crystal growth furnace, and the crystal is grown by the descending method to obtain xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 crystal.
5. The method for preparing a lead-based ferroelectric crystal material with a high voltage merit according to claim 4, characterized in that: The medium used in step S1 is anhydrous ethanol or deionized water. Preferably, the drying temperature in S1 is 100-150°C. Preferably, the calcination temperature in step S1 is 800-1100° C., and the calcination time is 2-8 hours.
6. The method for preparing a lead-based ferroelectric crystal material with a high voltage merit according to claim 4, characterized in that: In step S2, xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 powder is ground and dried again, including the following steps: xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 powder is crushed, added with grinding media for grinding, dried, and then ground again.
7. The method for preparing a lead-based ferroelectric crystal material with a high voltage merit according to any one of claims 4 to 6, characterized in that: The temperature of the re-calcination in step S2 is 800-1200° C., and the calcination time is 2-8 hours.
8. The method for preparing a lead-based ferroelectric crystal material with a high voltage merit according to any one of claims 4 to 6, characterized in that: Step S3 includes the following steps: The xPb(Ho 1 / 2 Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 polycrystalline material is placed in a crucible and then placed in a crystal growth furnace, the temperature of the crystal growth furnace is raised to above the melting point of the raw material, and the temperature is kept for 5 to 15 hours, and then the crucible is lowered at a rate of 1 to 2 cm / day to grow crystals; After a growth period of 15-25 days, the temperature was cooled to room temperature at a rate of 10-40°C / hour to obtain xPb(Ho 1 / 2Nb 1 / 2 )O3-(1-xy)Pb(Mg 1 / 3 Nb 2 / 3 )O3-yPbTiO3 crystal.
9. The method for preparing a lead-based ferroelectric crystal material with a high voltage merit according to any one of claims 4 to 6, characterized in that: Before step S1, the method also includes the step of preparing MgNb2O6 powder and HoNbO4 powder. Preferably, the preparation of MgNb2O6 powder comprises the following steps: The raw materials of Mg salt or oxide and Nb oxide are added to a grinding medium, ground, dried and crushed, and calcined at a temperature of 1000-1300° C. for 1-5 hours to obtain MgNb2O6 powder. Preferably, the preparation of HoNbO4 powder comprises the following steps: Ho oxide and Nb oxide are added to a grinding medium, ground, dried and crushed, and calcined at a temperature of 1000-1300° C. for 1-5 hours to obtain HoNbO4 powder.
10. Use of the lead-based ferroelectric crystal material with high voltage electrical merit as described in any one of claims 1 to 3 or the lead-based ferroelectric crystal material with high voltage electrical merit prepared by the method described in any one of claims 4 to 9 in piezoelectric devices, for example, as a sensor or a piezoelectric energy collector.